PENGARUH PERKEMBANGAN TEKNOLOGI HOME INDUSTRY KRUPUK PULI UNTUK MENINGKATKAN PENDAPATAN MASYAKARAT DI DESA SARIROGO - Yoga bayu nugroho; Norma Rosyidah (STAI AN-NAJAH INDONESIA MANDIRI, 2022)
Crackers have become a product that is characteristic of a region, now crackers are not only a complement to food, in Sarirogo village, Sidoarjo sub-district, the district has the potential for a cracker puli household business, the cracker puli business in Sarirogo village has problems with drying crackers which are hampered came the rainy season, which caused production to drop very drastically, almost 60% of total production which fell compared to summer and normal days before the rainy season came, the next problem was the lack of human resource management, product marketing that was not yet widespread in the digital world, not yet structured bookkeeping and recording. The solutions proposed for solving the partner's problems: the first is by designing and manufacturing tools for drying crackers, looking for new employees who are ready and have the determination to work hard, creating an online buying and selling account for marketing crackers on social media, conducting bookkeeping training on puli cracker partners Keywords: Technology Development, Home Industry, income References Ariani, Ariani, and Mohamad Nur Utomo. “KAJIAN STRATEGI PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KOTA TARAKAN.” Jurnal Organisasi dan Manajemen 13, no. 2 (September 27, 2017): 99–118. https://doi.org/10.33830/jom.v13i2.55.2017. Fawaid, Achmad, and Erwin Fatmala. “Home Industri Sebagai Strategi Pemberdayaan Usaha Mikro Dalam Meningkatkan Financial Revenues Masyarakat.” Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan 14, no. 1 (June 21, 2020): 109. https://doi.org/10.35931/aq.v14i1.342. Idayu, Riyanthi, Mohamad Husni, and Suhandi Suhandi. “Strategi Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) Untuk Meningkatkan Perekonomian Masyarakat Desa di Desa Nembol Kecamatan Mandalawangi Kabupaten Pandeglang Banten” 7, no. 1 (July 6, 2021): 73. https://doi.org/10.35906/jm001.v7i1.729. Nurzamzami, Ayatusyifa, and Edward H Siregar. “Peningkatan Daya Saing UMKM Alas Kaki di Kecamatan Ciomas, Kabupaten Bogor dan Implikasinya terhadap Strategi Pemasaran,” no. 1 (2014): 15. Pangestika, Putri, and Imam Santoso. “The Development Strategy of Potential Business of Micro, Small, and Middle Enterprises (MSMEs) with Financial Credit Supporting Program (Case Study: MSMEs of XYZ Regency)” 5, no. 2 (August 30, 2016): 84–95. Rahmadani, Suci. “Analisis Strategi Pengembangan UMKM dalam Meningkatkan Pendapatan Masyarakat Desa Padang Brahrang Kec.Selesai Kab.Langkat (Studi Kasus Pada Home Industri Krupuk & Keripik).” Maslahah: Jurnal Pengabdian Masyarakat 2, no. 3 (October 23, 2021): 115–29. https://doi.org/10.56114/maslahah.v2i3.160. Utami, Rahayu Sri, Handeo Ginting, and Muhammad Khairil. “Analisis Dampak Covid-19 Terhadap Perkembangan Umkm (Studi Kasus : Home Industri Kopi Sikarta) Di Desa Sialang Kecamatan Bangun Purba Kabupaten Deli Serdang.” JURNAL WIDYA 1, no. 1 (April 5, 2020): 30–42. https://doi.org/10.54593/awl.v1i1.40.